Determinants of School Well-Being Among Students in 3T Areas of Sorong Regency: A Mixed-Methods Study - Amalia Muthmainnah Lundeto; Adinda Shofia; Siti Hardianti; Dewi Fortuna Septiantika (Journal of Educational, Health and Community Psychology, 2026)
This study examined school well-being and its protective and risk factors among senior high school students in underdeveloped, frontier, and outermost (3T) schools in Sorong Regency. Using a sequential explanatory mixed-methods design, the quantitative phase involved 413 students from 15 schools and was analyzed using descriptive statistics and confirmatory factor analysis. The instrument was adapted from Konu and Rimpelä’s school well-being framework, comprising four dimensions: having, loving, being, and health. Of the initial 24 items, 14 were retained after construct validity testing. The qualitative phase involved interviews with students, teachers, parents, and representatives of the local education office, and the data were analyzed thematically. The quantitative findings indicated that students’ school well-being was at a moderate level, with the greatest challenges observed in the health and having dimensions. The qualitative findings revealed four major themes: deprivation and access barriers in the having dimension; social connectedness in the loving dimension; stagnation and contextual adaptation in the being dimension; and vulnerability and limited health support in the health dimension. The main protective factors included social support, positive teacher–student relationships, and students’ adaptive capacity, whereas the major risk factors were limited facilities, restricted access, less engaging instructional methods, and limited opportunities for self-development. These findings highlight the need for holistic interventions that address both physical and psychosocial conditions to improve school well-being among students in 3T schools.